KALIBRASI SEISMOMETER BBVS-120:G05402VS DENGAN METODE KOMPARASI - B. Simbolon; M. Delina; B. Heryanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Calibration has been performed SeismometerBBVS-120: G05402VS in Calibration Laboratory Meteorology and Geophysics Kemayoran. Seismometer calibration performed with comparative method which compares the seismometers are calibrated with similar seismometer. Seismometers placed parallel and adjacent to each other (Â± 10 cm) so that the movement of the land received by the seismometer is the same. Comparison data were processed using software comparison . As a result, a new sensitivity values obtained with the acquisition value of the sensitivity seismometer Horizontal EW 2142 V / m / s, Horizontal NS 2096 V / m / s and Vertical UD 2137 V / m / s. Based on the manufacturer's specifications, the seismometer BBVS-120: G05402VS had a sensitivity of 2000 V / m / s. In overall results of this calibration is still in both categories.Keywords: calibration, comparison, sensitivity.